PEMANFAATAN FLATFORM QUIZIZZ SEBAGAI MEDIA PEMBELAJARAN SENI TARI DALAM UPAYA MENINGKATKAN PARTISIPASI BELAJAR DI KELAS IX SMP TAMANSISWA KOTA PADANG SMP - Winda, Nisa; Alrizka Hairi Dilfa (Universitas Negeri Padang, 2026)
The background of this study arises from the low levels of student participation and engagement in dance education, which tends to be conventional and makes limited use of digital media. This research aims to analyze the use of the Quizizz platform as a learning tool in dance education to enhance the engagement of ninth-grade students at SMP Tamansiswa Kota Padang. The study employed a qualitative approach with a descriptive case study design. Data were collected through participant observation, in-depth interviews, and document analysis involving dance teachers and ninth-grade students. The findings indicate that the use of Quizizz creates a more engaging, interactive, and enthusiastic learning atmosphere, thereby increasing students’ attention, motivation, and participation in class. Therefore, the Quizizz platform has proven effective in promoting student participation in dance learning.